Possibilities and limitations of using various light sources in the treatment of acne vulgaris - Brzezińska, Natalia Ewa; Roter, Gustaw; Szczerkowska-Dobosz, Aneta (Dermatology Review/Przegląd Dermatologiczny, 2023)
Acne vulgaris is a chronic inflammatory skin condition with a high global prevalence. Light-based therapies can be used in acne treatment on account of their good safety profile, lack of potential for developing resistance, and mechanism of action. Despite variations in research methodologies and diverse findings among researchers, numerous clinical studies have shown a statistically significant improvement in the skin condition of acne patients treated with light. In the majority of studies, the follow-up period is comparatively short, preventing the evaluation of long-term effects of therapy. This paper examines the literature on the effects of various light therapies (based on LED devices, photodynamic therapy, intense pulsed light, and laser therapy), on the clinical signs of acne.